The Internationalization of the Academy Changes, Realities and Prospects - Huang, Futao; Finkelstein, Martin; Rostan, Michele; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2014)
This volume provides a nuanced empirical assessment of the extent to which the academic profession is internationalized at the beginning of the 21st century. It indicates which are the most internationalized academic activities, and focuses on specific topics such as physical mobility for study or professional purposes, teaching abroad or in another language, research collaboration with foreign colleagues, and publication and dissemination outside one$1 (Bs native country or in another language. It places the main theme in the wider context of the history of higher education$1 (Bs internationalization. It provides explanations on what drives and deters academics from international activity, and documents some of the consequences that internationalization has on academic work and productivity. This study is based on a survey of 25,000 academics working at higher education institutions in 18 countries and Hong Kong on five continents. Comparing data from the 1992 Carnegie International study to the 2007 CAP survey, relying on respondents$1 (Bperceptions of change, and comparing different academic generations, it offers valuable insights on changes in the internationalization of the academy.s
Acknowledgements -- 1. The Internationalization of the Academic Profession -- 2. Concepts and Methods -- 3. A Profile of CAP Participating Countries and a Global Overview of Academic Internationalization in 2007-2008 -- 4. Internationalization of the Academy: Rhetoric, Recent Trends and Prospects -- 5. The International Mobility of Academic Staff -- 6. The International Dimension of Teaching and Learning -- 7. The Internationalization of Research -- 8. Regionalization of Higher Education and the Academic Profession in Asia, Europe and North America -- 9. Gender and Faculty Internationalization -- 10. Internationalization and the New Generation of Academics -- 11. Patterns of Faculty Internationalization: A Predictive Model -- 12. The Internationalization of the Academy: Findings, Open Questions and Implications -- Appendix -- Notes on Contributors.
Keywords: Education; Education, Higher; Education; Higher Education; International and Comparative Education; Sociology of Education